2018
DOI: 10.1007/s12550-018-0307-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response of growing German Holstein bulls to a vaccination against bovine viral diarrhea virus (BVDV) is influenced by Fusarium toxin exposure in a non-linear fashion

Abstract: The Fusarium toxin deoxynivalenol (DON) is a frequent contaminant of feedstuffs and is supposed to interfere with immune responses. As the relevance for growing bulls is less clear than for other livestock, the trial was designed according to the dose-response principal with a control group fed a diet with background contamination (CON, 0.36 mg DON per kilogram dry matter [DM]) and three groups with increasing concentrations of DON (mg/kg DM); FUS I, 3.01; FUS II, 5.66; FUS III, 8.31. Half of each treatment gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The effects of DON on laboratory animal immunoglobulin levels has been previously reviewed [ 1 , 2 ], and has been shown to result in altered Ig production in a class-dependent manner. Furthermore, previous work has shown that disruptions to antibody production are an important nonlinear toxicological outcome in this species [ 8 , 12 , 13 , 14 , 15 ], a conclusion which these data further support.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The effects of DON on laboratory animal immunoglobulin levels has been previously reviewed [ 1 , 2 ], and has been shown to result in altered Ig production in a class-dependent manner. Furthermore, previous work has shown that disruptions to antibody production are an important nonlinear toxicological outcome in this species [ 8 , 12 , 13 , 14 , 15 ], a conclusion which these data further support.…”
Section: Resultssupporting
confidence: 80%
“…As such, research into simultaneous exposures to these compounds has increased, with special attention given to their long-term effects in livestock species that ultimately enter the human food chain. Ruminants, including cattle, are generally considered tolerant of these compounds, yet numerous studies document toxicity in this group of mammals [ 6 , 7 , 8 , 9 ]. For DON, this can include decreased feed consumption and alterations in the rumen such as decreased NDF digestibility; for FUM, changes in liver enzymes and markers related to metabolism have been noted [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced count of segmented neutrophils, which consequently affected the total leucocyte counts, was noticed in heifers exposed to DON at 3 ppm but not at 6 ppm. Similar results were observed when exposing Holstein bulls to increasing concentrations of DON (Dänicke et al, 2018). Dietary DON at 8.31 ppm induced higher neutrophil counts than lower level (i.e., 5.66 ppm).…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies and reviews examining the effects of DON or FUM on fattening/finishing beef cattle identified decreased rate of body weight gain, and toxicity to the liver, kidney and immune system as the main toxic endpoints (Baker and Rottinghaus, 1999;Dänicke et al, 2005Dänicke et al, , 2018EFSA, 2017EFSA, , 2018Osweiler et al, 1993). In the present study, we utilized an average concentration in the TMR of 1.7 mg DON and 3.5 mg FUM per kg TMR in the diet in a partial crossover study with 12 black Angus steers to examine the effects of these mycotoxins on overall beef cattle physiology, along with hepatic and immune function in more depth than previous works.…”
Section: Resultsmentioning
confidence: 99%